2018
DOI: 10.1007/s40265-018-0953-z
|View full text |Cite
|
Sign up to set email alerts
|

Treating Chronic Pain: An Overview of Clinical Studies Centered on the Buprenorphine Option

Abstract: The buprenorphine receptor binding profile is unique in that it binds to all three major opioid receptors (mu, kappa, delta), and also binds to the orphan-like receptor, the receptor for orphanin FQ/nociceptin, with lower affinity. Within the mu receptor group, buprenorphine analgesia in rodents is dependent on the recently discovered arylepoxamide receptor target in brain, which involves a truncated 6-transmembrane mu receptor gene protein, distinguishing itself from morphine and most other mu opioids. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 187 publications
(180 reference statements)
1
108
0
10
Order By: Relevance
“…Similarly, good quality, randomized studies in neuropathic pain patients are needed. In randomized trials of postoperative or osteoarthritis pain, buprenorphine was concluded to produce fewer respiratory complications, but equivalent analgesia to other opioids ( Davis et al, 2018 ), although the reason for the lack of ceiling analgesic effects in contrast to respiratory depression is unclear, and other studies reported high rate of drop-out due to nausea/vomiting ( Fishman and Kim, 2018 ). Together, as buprenorphine is successfully used for opioid maintenance therapy, the evidence for its analgesic superiority over other opioids in clinical setting appears moderate and more good quality comparative studies are needed ( Davis et al, 2018 ).…”
Section: Heteromers Bivalent and Multifunctional Ligandsmentioning
confidence: 99%
“…Similarly, good quality, randomized studies in neuropathic pain patients are needed. In randomized trials of postoperative or osteoarthritis pain, buprenorphine was concluded to produce fewer respiratory complications, but equivalent analgesia to other opioids ( Davis et al, 2018 ), although the reason for the lack of ceiling analgesic effects in contrast to respiratory depression is unclear, and other studies reported high rate of drop-out due to nausea/vomiting ( Fishman and Kim, 2018 ). Together, as buprenorphine is successfully used for opioid maintenance therapy, the evidence for its analgesic superiority over other opioids in clinical setting appears moderate and more good quality comparative studies are needed ( Davis et al, 2018 ).…”
Section: Heteromers Bivalent and Multifunctional Ligandsmentioning
confidence: 99%
“…The bioavailability of oral buprenorphine is less than 15%, resulting in the need for other routes of administration. 28 Table 1 provides an overview of the formulations, available strengths, frequency of administration, bioavailability, and extrapolated equivalent dose information. 29 High-dose buprenorphine therapy can be defined as any dose that equals or exceeds an equivalent dose of 24 mg of daily sublingual buprenorphine, whereas low-dose therapy can be defined by any equivalent daily dose less than or equal to 8 mg sublingually.…”
Section: Formulation and Dosingmentioning
confidence: 99%
“…Buprenorphine and methadone are indicated for opioid use disorders and are also effective analgesics, suggesting they may have an important role in patients with cancer‐related pain and NMOU. Canadian guidelines for the management of patients with chronic non–cancer‐related pain and substance use disorder recommend opioid agonist treatment with buprenorphine‐naloxone as the preferred treatment; however, methadone is also acceptable.…”
Section: Management Strategiesmentioning
confidence: 99%